2021
DOI: 10.1167/iovs.62.13.25
|View full text |Cite
|
Sign up to set email alerts
|

Luminance Thresholds and Their Correlation With Retinal Structure in X-Linked Retinoschisis

Abstract: Purpose To provide a comprehensive analysis of light- and dark-adapted luminance thresholds and their associations with retinal structure in X-linked retinoschisis (XLRS). Methods Nine subjects with XLRS and 10 visually-normal individuals participated. Threshold was measured at 15 locations along the horizontal meridian of the visual field at several adaptation levels (5 × 10 − 5 to 50 cd/m 2 ) after d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A recent perimetry study examined luminance thresholds across the visual field under a broad range of adaptation levels (dark-adapted scotopic conditions to 50 cd/m 2 photopic conditions) in a group of subjects who had XLRS. 6 This study found that the pattern of threshold elevation in XLRS was complex, with the extent of abnormality depending on both the adaptation level and the visual field location tested. Interestingly, thresholds measured in the macula of the XLRS subjects were similar to thresholds measured in the peripheral field of control subjects.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…A recent perimetry study examined luminance thresholds across the visual field under a broad range of adaptation levels (dark-adapted scotopic conditions to 50 cd/m 2 photopic conditions) in a group of subjects who had XLRS. 6 This study found that the pattern of threshold elevation in XLRS was complex, with the extent of abnormality depending on both the adaptation level and the visual field location tested. Interestingly, thresholds measured in the macula of the XLRS subjects were similar to thresholds measured in the peripheral field of control subjects.…”
mentioning
confidence: 79%
“…This finding supports previous data suggesting that macular function in subjects with XLRS is functionally similar to the peripheral field function of visually normal individuals. 6 , 19 Specifically, Alexander et al 19 reported contrast sensitivity and contrast discrimination abnormalities in subjects with XLRS and that the pattern of abnormality in these subjects could be simulated in control observers by testing at a parafoveal locus. The eye tracking data presented in Supplemental Figure S1 that show stable foveal fixation indicate that eccentric viewing does not explain the threshold elevations in the present sample of XLRS subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations